Online Social Networks : Human Cognitive Constraints in Facebook and Twitter Personal Graphs - Arnaboldi, Valerio ... [et al.]. (Amsterdam : Elsevier, 2015)
Online Social Networks: Human Cognitive Constraints in Facebook and Twitter provides new insights into the structural properties of personal online social networks and the mechanisms underpinning human online social behavior. As the availability of digital communication data generated by social media is revolutionizing the field of social networks analysis, the text discusses the use of large- scale datasets to study the structural properties of online ego networks, to compare them with the properties of general human social networks, and to highlight additional properties.
Human social networks -- Tie strength and ego network structure in Facebook -- The structure of ego network in Twitter -- Evolutionary dynamics in Twitter ego networks
Keywords: Online social networks; Social media; Online social networks; Social media